A cupin domain-containing protein with a quercetinase activity (VdQase) regulates Verticillium dahliae's pathogenicity and contributes to counteracting host defenses - El Hadrami, Abdelbasset; Islam, Md. Rashidul; Adam, Lorne R.; Daayf, Fouad (Frontiers in Plant Science, 2015)
We previously identified rutin as part of potato root responses to its pathogen Verticillium dahliae. Rutin was directly toxic to the pathogen at doses greater than 160 μM, a threshold below which many V. dahliae pathogenicity-related genes were up-regulated. We identified and characterized a cupin domain-containing protein (VdQase) with a dioxygenase activity and a potential role in V. dahliae-potato interactions. The pathogenicity of VdQase knock-out mutants generated through Agrobacterium tumefasciens-mediated transformation was significantly reduced on susceptible potato cultivar Kennebec compared to wild type isolates. Fluorescence microscopy revealed a higher accumulation of flavonols in the stems of infected potatoes and a higher concentration of rutin in the leaves in response to the VdQase mutants as compared to wild type isolates. This, along with the HPLC characterization of high residual and non-utilized quercetin in presence of the knockout mutants, indicates the involvement of VdQase in the catabolism of quercetin and possibly other flavonols in planta. Quantification of Salicylic and Jasmonic Acids (SA, JA) in response to the mutants versus wild type isolates revealed involvement of VdQase in the interference with signaling, suggesting a role in pathogenicity. It is hypothesized that the by-product of dioxygenation 2-protocatechuoylphloroglucinolcarboxylic acid, after dissociating into phloroglucinol and protocatechuoyl moieties, becomes a starting point for benzoic acid and SA, thereby interfering with the JA pathway and affecting the interaction outcome. These events may be key factors for V. dahliae in countering potato defenses and becoming notorious in the rhizosphere.